DEVELOPMENT OF PROFESSIONAL COMPETENCIES OF PRE-SERVICE MILITARY EDUCATION STUDENTS BASED ON INFORMATION AND COMMUNICATION TECHNOLOGIES - Lieutenant Colonel Egamberdiyev Ilhomjon Yigitaliyevich (Galaxy International Interdisciplinary Research Journal, 2022)
There is no need to emphasize today the role and importance of pre-service training of future soldiers and officers of our army, the importance of their conscious approach to choosing this difficult profession. Therefore, today it is important to systematically transfer knowledge about modern technologies and information and communication in all areas, including pre-service military education. In this article, the author discusses in detail the reforms and analysis of the development of professional competencies of students of pre-service military education based on information and communication technologies.